The effect of phytochemicals in N-methyl-N-nitro-N-nitroguanidine promoting the occurrence and development of gastric cancer - Lu, Ling; Chen, Bei; Zhang, XinYi; Xu, Yumeng; Jin, Longtao; Qian, Hui; Liang, Zhao feng (Frontiers in Pharmacology, 2023)
Gastric cancer is a common malignant tumor with low early diagnosis rate and poor prognosis. N-methyl-N-nitro-N-nitroguanidine (MNNG) is one of the most important inducing factors of gastric cancer. Phytochemicals are healthy active substances derived from vegetables, fruits, nuts, tea, Chinese herbal medicines and other plants. Phytochemicals has been showed to be a very promising approach to prevention and treatment of gastric cancer. It has been found that phytochemicals have protective effects against MNNG-induced gastric cancer via inhibit the cell proliferation, enhance immunity, suppress cell invasion and migration, induce apoptosis and autophagy, block angiogenesis inhibit Helicobacter pylori infection, regulate metabolism and microbiota. The effect of phytochemicals in the occurrence and development of gastric cancer induced by MNNG has attracted more and more attention. In order to better understand the relationship between phytochemicals and MNNG-induced gastric cancer, we briefly summarize the roles and functions of phytochemicals in gastric cancer induced by MNNG. This review may help guide the public to prevent the occurrence and development of MNNG related gastric cancer through phytochemicals.